2014
DOI: 10.1103/physrevb.90.214303
|View full text |Cite
|
Sign up to set email alerts
|

Anharmonicity and atomic distribution of SnTe and PbTe thermoelectrics

Abstract: The structure and lattice dynamics of rock-salt thermoelectric materials SnTe and PbTe are investigated with single crystal and powder neutron diffraction, inelastic neutron scattering (INS), and first-principles simulations. Our first-principles calculations of the radial distribution function (RDF) in both SnTe and PbTe show a clear asymmetry in the first nearest-neighbor (1NN) peak, which increases with temperature, in agreement with recent experimental reports. We show that this peak asymmetry for the 1NN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 56 publications
3
57
0
2
Order By: Relevance
“…A clear theoretical explanation of the anomalous stiffening of the LO mode with increasing temperature was only given last year by Li et al 13 . At the same time, there is a very strong anharmonicity between the ferroelectric transverse mode and the longitudinal acoustic mode, which was studied in part by Li et al in a follow up paper 21 .…”
Section: -4mentioning
confidence: 94%
“…A clear theoretical explanation of the anomalous stiffening of the LO mode with increasing temperature was only given last year by Li et al 13 . At the same time, there is a very strong anharmonicity between the ferroelectric transverse mode and the longitudinal acoustic mode, which was studied in part by Li et al in a follow up paper 21 .…”
Section: -4mentioning
confidence: 94%
“…Among thermoelectrics, PbTe and SnTe have drawn attention due to some of their interesting properties [12][13][14][15][16][17] . Both systems have high figures of merit, turning them into effective thermoelectrics.…”
Section: Introductionmentioning
confidence: 99%
“…Classical MD simulations of 512-atom supercells based on ab initio inter-atomic force constants (IFCs) 13 also reproduced the phonon spli ing and identi ed unusually large cubic IFCs along the ⟨100⟩ direction as the source. In contrast, later studies 14,15 combining ab initio MD simulations (using 512 atom supercells and the PBE functional in the VASP code) with single-crystal and powder neutron di raction and inelastic neutron sca ering suggested that a sharp resonance in the phonon self energy caused by nesting of phonon dispersions could combine with the anharmonicity to produce the large phonon spli ing. Once again, however, while the simulated nearest-neighbor Pb-Te PDF peak showed increasing asymmetric character with temperature, the highly-non-Gaussian lineshapes and anomalous shi s in peak centroid were not captured.…”
mentioning
confidence: 99%